Pengaruh Ekuitas Merek terhadap Minat Beli Ulang Produk Emina Pada Generasi Z - Winna Algustin; Rindang Matoati (Jurnal Bisnis dan Ekonomi, 2020)
Indonesian cosmetics industry has increased as population is predominantly influenced by generation Z. Emina is a new local cosmetic brand product that needs to be strengthen its brand equity in order to enchance both competitiveness and repurchase intention in the future. This study aimed to determine the characteristics of generation Z customers, to find out brand equity, and to determine the effect of brand equity on repurchase intention in generation Z customers of Emina. The study was conducted in the city and district of Bogor with criteria for women aged 12-24 years purchased Emina products at least once with total of respondent are 290. The sampling method used a purposive sampling technique with analytical tools descriptive analysis, and multiple linear regression analysis with SPSS version 25. The results of this research show that all brand equity variables simultaneously influenced the repurchase intention. Partially, brand awareness, perceived quality, and brand loyalty variables significantly influence repurchase intention